Demand Analysis for Tourism in African Local Communities - World Bank Group (World Bank, Washington, DC, 2018)
This report aims to provide a market overview that describes the main characteristics and size of current and future demand for tourism products delivered by and based in local communities in Africa. If demand is better understood, supply can be better developed and better placed to take advantage of the market access opportunities offered by the growth in digital platforms. Increased supply that is performing well will yield development results for marginalized communities and help to increase shared prosperity.